2015
DOI: 10.1111/1754-9485.12403
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dosimetric impact of breast tissue expanders on post‐mastectomy radiotherapy

Abstract: Dose is attenuated in the 'shadow' of the tissue expander port in patients receiving PMRT. This is likely to be clinically insignificant for most, but centres should undertake appropriate measurements before utilising TPS predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
2
21
1
1
Order By: Relevance
“…Gee et al25 reported an average 7% dose reduction to skin surface in a sample of PMRT patients with tissue expanders using opposing tangent beams, and Chatzigiannis et al17 reported 7% to 13% dose reduction with the expander in place for two 6 MV tangential photon beams, and our study showed 5.5%~6.6% dose reduction in the skin area for the conventional plan. The dose reduction increased to 15.6%~15.8% when we only used one beam in the conventional plan, which is close to 22% reduction reported by Damast et al16 for a single 6 MV beam.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Gee et al25 reported an average 7% dose reduction to skin surface in a sample of PMRT patients with tissue expanders using opposing tangent beams, and Chatzigiannis et al17 reported 7% to 13% dose reduction with the expander in place for two 6 MV tangential photon beams, and our study showed 5.5%~6.6% dose reduction in the skin area for the conventional plan. The dose reduction increased to 15.6%~15.8% when we only used one beam in the conventional plan, which is close to 22% reduction reported by Damast et al16 for a single 6 MV beam.…”
Section: Resultssupporting
confidence: 56%
“…However, it seems that the tissue expander used in this study was the most popular type used in the US and other countries according to literature14, 15, 16, 17, 24, 25, 31 and Pinnacle is one of the most widely used TPS worldwide, which means our model is applicable to most clinics. The methodology used in this study is generally applicable and clinics that use different brands of tissue expanders or TPS could create their own model and improve their dosimetric accuracy by using our approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generic reference to ‘breast reconstruction’ was intended to capture all articles addressing the type and timing of breast reconstruction. Two authors independently reviewed abstracts of all studies published between 1985 and 2014, and the full texts of those studies published in 2015–2017. Levels of clinical evidence (LoE) were evaluated for each publication and scored from I to V by employing Oxford criteria.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 For patients with TE that uses an IMP, the known inaccuracies of convolution algorithms may have a limited clinical impact. 21,22 The high-density magnet is generally more than 1 cm away from patient tissue, so inaccuracies in lateral scatter dose are confined to the saline filling the TE and the IMP itself. AAA's underestimation of attenuation through the IMP might affect the accuracy of the dose calculated in the "dose shadow" region.…”
Section: Introductionmentioning
confidence: 99%